Unique Surgical Issues in the Management of a Giant Retroperitoneal Schwannoma and Brief Review of Literature - Santhosh Kuriakose; Syam Vikram; Surij Salih; Satheesan Balasubramanian; Nizamudeen Mangalasseri Pareekutty; Sangeetha Nayanar (Case Reports in Medicine)
Ancient Schwannoma, though benign, can cause diagnostic dilemma because of its clinical presentation and imaging features. We report the management of a giant retroperitoneal schwannoma in a 19-year-old young lady who presented with lower abdominal distension. CT scan reported a large heterogenous lesion in the abdominopelvic retroperitoneum (42 cm × 16 cm × 16 cm) as a malignant tumor. The unique problems we encountered were the enormous size, the location of major part of the tumor in the pelvis, the need for fertility preservation, the external iliac vessels stretching over the tumor making mobilization surgically demanding, and the prospects of neurological deficits. An en bloc resection of schwannoma with common iliac, external iliac and internal iliac veins, internal iliac artery, femoral and obturator nerves, and iliopsoas muscle was done maintaining oncological principles. External iliac artery that was cut to facilitate tumor mobilization was reanastomosed at the end of the procedure. Postoperatively patient had uneventful recovery with patchy sensory loss, foot drop, and quadriceps weakness which was rehabilitated with a foot drop splint and active physiotherapy.